Effectiveness of Hydro Pressure Techniques on Biofilm Removal for Diabetic Ulcuses Patients at Wocare Indonesia - Naziyah, Naziyah; Said, Mohamed Saifulaman Mohamed; Said, Faridah Mohd; Hidayat, Rizki (International Journal of Nursing Information, 2024)
Diabetic ulcer wounds that occur in patients with diabetes that involve disorders of the peripheral and autonomic nerves. Diabetic wounds are a significant complication of diabetes and a global public health problem. There has been no wound-washing intervention using the hydro pressure technique as a wound washer tool for diabetic ulcer Biofilm. The aim is to determine the effect of the hydro pressure technique as a wound washer on biofilm for diabetic foot ulcer patients. The methodology research in this study used the pre-experimental method with a pre-test and post-test approach. The sampling technique was carried out using total sampling. The total sampling of this study is 25 respondents in criteria inclusion in this area. The research instrument used was a biofilm observation sheet. The statistical tests used were univariate and bivariate, using paired sample t-tests. The results show that there is a significant difference between the values of the biofilm observation sheet before hydro pressure is performed and after hydro pressure is performed on diabetic ulcer patients. The hydro pressure technique can reduce the average value of biofilm in the wound healing process. This research contributes to recommending that diabetic ulcer sufferers use the hydro pressure technique to remove biofilm in the wound healing process.